2006
DOI: 10.1111/j.1398-9995.2006.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered recombinant ovomucoid third domain can desensitize Balb/c mice of egg allergy

Abstract: The purpose of this study was to determine the in vivo desensitization efficacy of a hypoallergenic variant of egg white ovomucoid third domain (DIII) in Balb/c mice model. We mapped the immunodominant B-cell epitopes of ovomucoid in Balb/c mice. A hypoallergenic ovomucoid third domain (GMFA) mutant isoform having ablated allergenicity against egg allergic patient's sera was used to desensitize DIII-sensitized Balb/c mice by intraperitoneal injections. Ovomucoid DIII generated high levels of plasma histamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…3A, p,0.05). The total IgE level in allergy mice was lower than those in previous studies (20,27). The above results were consistent with what we had predicted, since oral administration before sensitization suppressed the increase in total IgE (28,29).…”
Section: Discussionsupporting
confidence: 82%
“…3A, p,0.05). The total IgE level in allergy mice was lower than those in previous studies (20,27). The above results were consistent with what we had predicted, since oral administration before sensitization suppressed the increase in total IgE (28,29).…”
Section: Discussionsupporting
confidence: 82%
“…Although murine peanut allergy models have been reported to accurately resemble human anaphylaxis [20], the clinical symptom scores were lower in BALB/c [20] and C3H/HeOuJ mice [30] receiving peanut orally than systemically. As shown elsewhere, intraperitoneal sensitization has proven successful [25,31], food allergens have been widely used in models of systemic anaphylaxis [14,32,33]; both classic and alternative pathways were activated in a mouse model of systemic sensitization [8]. As our primary aim was to study systemic anaphylaxis (activating IgE and IgG pathways) expressed by sharp clinical and immunological responses in both strains, we developed a systemic sensitization protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Actually our previous studies demonstrated that various allergens such as ovalbumin, tropomyosin, α-lactoglobulin, β-lactoglobulin, and casein structurally modified by gamma irradiation reduced a binding ability to IgE of allergic patients [5][6][7]10]. Their properties might be applied to manufacture of functional foods for allergic patients [7].…”
Section: Discussionmentioning
confidence: 97%